2006
DOI: 10.1093/annonc/mdj024
|View full text |Cite
|
Sign up to set email alerts
|

Is CT scan still necessary for staging in Hodgkin and non-Hodgkin lymphoma patients in the PET/CT era?

Abstract: The addition of PET/CT to CT changed the management decisions in approximately a quarter of NHL and a third of HD patients, mostly in early disease stages. Thus, PET/CT performed as the initial staging procedure may well obviate the need for additional diagnostic CT in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(80 citation statements)
references
References 23 publications
5
70
0
4
Order By: Relevance
“…PET-CT altered staging in 20% of patients compared with the standard approach, which is at variance with earlier reports that suggested stage change occurred more often in patients with early stage rather than advanced disease. 10,20 Upstaging occurred more frequently than downstaging, with extranodal disease accounting for 74% of the upstaged scans, mostly due to an increased sensitivity of PET for detecting bone marrow involvement. Baseline and response scans were compared, and the findings were correlated with other imaging, where available, to determine the etiology of lesions that accounted for the discrepancy in stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PET-CT altered staging in 20% of patients compared with the standard approach, which is at variance with earlier reports that suggested stage change occurred more often in patients with early stage rather than advanced disease. 10,20 Upstaging occurred more frequently than downstaging, with extranodal disease accounting for 74% of the upstaged scans, mostly due to an increased sensitivity of PET for detecting bone marrow involvement. Baseline and response scans were compared, and the findings were correlated with other imaging, where available, to determine the etiology of lesions that accounted for the discrepancy in stage.…”
Section: Discussionmentioning
confidence: 99%
“…3,10,20 The truth as to whether lesions identified only on PET represent lymphoma is difficult to determine as biopsy of discrepant lesions is rarely performed. Correlative imaging, treatment response, follow-up, biopsy, or a combination usually serves as a reference standard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positron emission tomography (PET), increasingly combined with computed tomography (PET-CT), is now a routine part of staging DLBCL, owing to its ability to accurately evaluate both nodal and extranodal disease sites (including skeletal involvement), assign stage, and quantify prognosis. [4][5][6][7] Recently, a large retrospective study of marrow disease in DLBCL cases treated with R-CHOP (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone) reported that histologic evidence of DLBCL in staging marrow biopsy adversely affected overall survival (OS) and event-free survival, independent of the IPI. 8 We first examined PET as a method to assess bone marrow involvement in Hodgkin lymphoma (HL) and NHL in 1998 9 and reported that bone marrow involvement in both diseases may have a metastatic pattern, apparent as focal areas of increased 18F-fluorodeoxyglucose (FDG) uptake, or a more diffuse pattern of involvement with uniform FDG uptake throughout the marrow space.…”
Section: Introductionmentioning
confidence: 99%
“…This probably results from the higher costs of PET-CT compared to CT, the small number of PET-CT centers in the region, and the lack of well-defined recommendations concerning PET-CT implementation in routine practice. It is noteworthy that in one recent study PET-CT imaging -in comparison with CT alone -was shown to upstage the disease among patients initially diagnosed as stage I or II [15]. However, the official recommendations concerning the use of PET-CT in initial HL staging are slightly inconsistent.…”
Section: Discussionmentioning
confidence: 99%